Macrophage Polarization and Plasticity in Systemic Lupus Erythematosus - Ahamada, Mariame Mohamed; Jia, Yang; Wu, Xiaochuan (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is an autoimmune disease that attacks almost every organ. The condition mostly happens to adults but is also found in children, and the latter have the most severe manifestations. Among adults, females, especially non-Caucasian, are mostly affected. Even if the etiology of SLE remains unclear, studies show a close relation between this disease and both genetics and environment. Despite the large number of published articles about SLE, we still do not have a clear picture of its pathogenesis, and no specific drug has been found to treat this condition effectively. The implication of macrophages in SLE development is gaining ground, and studying it could answer these gaps. Indeed, both in vivo and in vitro studies increasingly report a strong link between this disease and macrophages. Hence, this review aims to explore the role of macrophages polarization and plasticity in SLE development. Understanding this role is of paramount importance because in-depth knowledge of the connection between macrophages and this systemic disease could clarify its pathogenesis and provide a foundation for macrophage-centered therapeutic approaches.